Analisis Perilaku Adopsi Livin Merchant Pada Pelaku UMKM di Surabaya Raya Menggunakan Model UTAUT2 - Medica N Zakiah; Asif Faroqi; Rafika Rahmawati (LKP Unity Academy, 2025)
The development of digital technology has encouraged the transformation of financial services in the micro, small, and medium enterprises (MSMEs) sector, one of which is through the use of the Livin’ Merchant by Mandiri application. However, the adoption process of digital services still faces several challenges, such as low technological literacy, risks associated with application usage, and low trust in system security and banking institutions. This study aims to analyze the factors influencing the adoption behavior of Livin’ Merchant among MSME actors in Greater Surabaya using the modified Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model with the addition of perceived security, perceived risk, institution trust, and technology trust variables. This study employed a quantitative approach through a survey of 521 MSME actors using Livin’ Merchant in Greater Surabaya. The data were analyzed using Partial Least Square-based Structural Equation Modeling (SEM-PLS) with the assistance of SmartPLS 4.0 software. The results indicate that performance expectancy, social influence, hedonic motivation, price value, perceived security, and institution trust have a positive and significant effect on behavioral intention. In addition, facilitating conditions have a positive and significant effect on use behavior, while perceived risk has a negative and significant effect on use behavior. This study concludes that application benefits, social support, system security, and trust in banking institutions are important factors in increasing the adoption of Livin’ Merchant among MSME actors in Greater Surabaya.